2020
DOI: 10.9739/tjvs.2020.749
|View full text |Cite
|
Sign up to set email alerts
|

The same clinical effect, with fewer complications and higher patient comfort, can be achieved with lower doses of N-butyl cyanoacrylate in endovenous ablation therapy: A prospective, randomized study

Abstract: Objectives: This study aims to investigate the therapeutic effect of N-butyl cyanoacrylate (NBCA) administration on the treatment success and patient comfort in patients with venous insufficiency. Patients and methods:Between March 2019 and June 2019, a total of 80 patients (29 males, 51 females; mean age 49.6±12.0 years; range, 25 to 81 years) diagnosed with great saphenous vein incompetence and underwent endovenous ablation with <1 mL or >1.5 mLNBCA were included in this prospective, randomized study. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Furthermore, Tang et al [19] reported an acellular foreign body reaction in the adventitia tissue suggesting that possible extravasation of the NBCA should be taken into consideration. In their series of VV patients, Acıpayam et al [20] demostrated that a lower than 1 mL dose of NBCA was related to a fewer complication ratio and greater patient satisfaction at the end of the first month following the procedure. Thus, studies established with various dosing regimen of NBCA are required to consider the appropriate dosing for each individual in order to lower the complication rate and obtain a greater procedure efficiency.…”
Section: 'O-#'/+l'/4567/+#'"+'2+/ =2/>/??[a! 7o+'#/+l'/4567/+#'"+'2+/ =2/>/??[a! !/9"and*'/ /mentioning
confidence: 99%
“…Furthermore, Tang et al [19] reported an acellular foreign body reaction in the adventitia tissue suggesting that possible extravasation of the NBCA should be taken into consideration. In their series of VV patients, Acıpayam et al [20] demostrated that a lower than 1 mL dose of NBCA was related to a fewer complication ratio and greater patient satisfaction at the end of the first month following the procedure. Thus, studies established with various dosing regimen of NBCA are required to consider the appropriate dosing for each individual in order to lower the complication rate and obtain a greater procedure efficiency.…”
Section: 'O-#'/+l'/4567/+#'"+'2+/ =2/>/??[a! 7o+'#/+l'/4567/+#'"+'2+/ =2/>/??[a! !/9"and*'/ /mentioning
confidence: 99%